2001
DOI: 10.1097/00001721-200103000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Acute hyperglycemia increases soluble P-selectin in male patients with mild diabetes mellitus

Abstract: The aim of this study was to examine if acute hyperglycemia (an oral glucose tolerance test) activates platelet function, endothelial cells or thrombin generation in diabetic patients and healthy controls. Eleven males with mild type II diabetes mellitus and 11 healthy male volunteers, matched for age and body mass index, were investigated before and after the glucose load. Soluble P-selectin, von Willebrand factor antigen and markers of thrombin generation in plasma were determined by immunoassays, and platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 38 publications
1
32
0
1
Order By: Relevance
“…It mediates platelet-leukocyte interaction in inflammatory and thrombotic reactions [25]. Diabetic patients have increased soluble P-selectin levels, especially when exposed to acute hyperglycemia [26]. Increased expression of P-selectin on the platelet surface was also suspected [27] and confirmed by more recent data [21,28].…”
Section: Mediators Of Diabetic Platelet Hyperreactivitymentioning
confidence: 77%
“…It mediates platelet-leukocyte interaction in inflammatory and thrombotic reactions [25]. Diabetic patients have increased soluble P-selectin levels, especially when exposed to acute hyperglycemia [26]. Increased expression of P-selectin on the platelet surface was also suspected [27] and confirmed by more recent data [21,28].…”
Section: Mediators Of Diabetic Platelet Hyperreactivitymentioning
confidence: 77%
“…Harding et al [33] showed that platelet-monocyte aggregates and CD40L levels were significantly elevated in type 1 diabetic subjects. Yngen et al [34] showed that acute hyperglycemia induced by oral glucose tolerance test led to elevated levels of sP-selectin in males with type 2 diabetes mellitus. Thus, among the several reasons for excess CAD in subjects with diabetes, increased platelet activation could be one.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies of the effect of acute hyperglycemia on platelet function in patients with DM are sparse. 13 The increased platelet activity is emphasized to play a role in the development of vascular complications of the metabolic disorder. Large platelets are hemostatically more active and are a risk factor for developing coronary thrombosis, leading to myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%